2014
DOI: 10.2519/jospt.2014.4809
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest and Interrater Reliability of the Functional Lower Extremity Evaluation

Abstract: The FLEE tests are considered clinically important for assessing lower extremity function by sports medicine personnel but are underused. The FLEE also is a reliable assessment tool. Future studies are required to determine if use of the FLEE to make return-to-play decisions may reduce reinjury rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 20 publications
1
37
1
2
Order By: Relevance
“…The THTD is the symmetry test with lower reproducibility, with poor reproducibility in the right leg (ICC 0.48 and CV 8.5%), but good in the left (ICC 0.76 and CV 8.7%). This contrasts with the excellent reproducibility found in university students of different sports, both collective and individual sports, with ICC 0.95 (0.92-0.97) [51]. The low reproducibility of the right leg could be again because of the dominance of RH, which makes the left leg the more stable, as this is the take-off limb with which the players of this sample preferably perform the attack jump hitting the ball with their right hand, which is consistent with the findings of Loturco et al [52].…”
Section: Discussioncontrasting
confidence: 73%
“…The THTD is the symmetry test with lower reproducibility, with poor reproducibility in the right leg (ICC 0.48 and CV 8.5%), but good in the left (ICC 0.76 and CV 8.7%). This contrasts with the excellent reproducibility found in university students of different sports, both collective and individual sports, with ICC 0.95 (0.92-0.97) [51]. The low reproducibility of the right leg could be again because of the dominance of RH, which makes the left leg the more stable, as this is the take-off limb with which the players of this sample preferably perform the attack jump hitting the ball with their right hand, which is consistent with the findings of Loturco et al [52].…”
Section: Discussioncontrasting
confidence: 73%
“…Single-leg hop performance was measured bilaterally using 4 separate hop tasks: single hop for distance, triple hop for distance, crossover hop for distance, and 6-m timed hop ( Figure 1 ), similar to previously recorded methods. 12 , 24 Each participant was given as many warm-up trials as needed until he or she felt comfortable completing the task. Testing always started with the uninvolved limb, and 3 trials were measured bilaterally for all 4 hopping tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Gustavsson et al 41 concluded that the one leg hop test for distance can discriminate between the injured and uninjured leg in patients with ACL injury. Furthermore, Haitzet al 45 studied normal values for the one leg hop test for distance as well as for the square hop test, and they did not find a side-to-side leg difference. In view of the published normative data the choice of cut off in the present study, 10 cm of side difference is not too small in order to determine a real side difference.…”
Section: Acl Injuries -Intrinsic Risk Factors In Alpine Skiingmentioning
confidence: 99%